Antiseptic effects of gumtect on saliva - Bondad-Palmario, Georgina G. (The Journal of the Philippine Dental Association)
The anti-microbial effect of Gumtect® to human saliva was tested by determining the means of ph change in a series of time interval for three hours. Thirty (30) volunteer test subjects who met the set criteria were utilized in the study after the informed consent forms were signed. Baseline data were measured as the subjects reported to the testing center every morning without performing any oral hygiene measures and not taking performing any oral hygiene measures and not taking breakfast or any beverage upon waking up. Salivary ph measurements were gathered in intervals of 30 minutes for three hours starting immediately after brushing with a full ribbon of the Gumtect® for one (1) minute followed by two (2) water-rinses which was designed as the 0 minute for three days in a period of three weeks.